ANALYSIS OF THE SCIENTIFIC LEARNING APPROACH IN ISLAMIC RELIGIOUS EDUCATION TO ENHANCE STUDENTS CRITICAL THINKING - Faisal, Faisal; Syahrullah, Syahrullah; Atmowidjoyo, Sutardjo; Abdurrohman, Firman Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The rapid advancement of knowledge and technology in the 21st century necessitates a shift in educational methods, particularly in Islamic Religious Education (PAI). Observations reveal a concerning gap in critical thinking skills among students at PKPPS Minhajurrosyidin Jakarta. Purpose: This study seeks to explore how a scientific approach can address this deficiency effectively. This study focuses on the application of the scientific approach in Islamic Religious Education (PAI) at PKPPS Minhajurrosyidin Jakarta, aiming to enhance students' critical thinking skills. The background highlights the low critical thinking skills among students, supported by pre-survey data. Method: The research method employed is a qualitative approach, including document studies, interviews, observations, and Focus Group Discussions (FGD). Result: The findings indicate that the scientific approach effectively improves student engagement, understanding, and motivation. The average student score increased from 70 to 85, and 21st-century skills such as critical thinking, communication, and collaboration developed well. Conclusion: The study concludes that the scientific approach not only enhances academic understanding but also non-academic skills, such as communication and collaboration. Suggestions for future research include applying the scientific approach in other educational contexts to test the generalization of these findings and developing more innovative learning strategies to improve the effectiveness of Islamic religious education in various educational settings